51 dalil Anwar jadi PM - Elias Hj Idris (Puchong, Selangor : SungaiBeruas Mart, 2008)
Political stance toward Anwar Ibrahim's chances of becoming prime minister of Malaysia.
Bibliografi: p. 255
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Anwar Ibrahim, -- Dato' Seri, -- 1947-; Politicians -- Malaysia -- Biography; Malaysia -- Politics and government